Avaliação da estrutura da entrevista investigativa com crianças - Stracke, Cristiane Borsatto (2013)
In the past years, there has been a considerable raise in the number of child sexual abuse complaints. Thereat, several studies have been developed about investigative interviewing of children with alleged abuse. The present dissertation has two sections about the topic of investigative interviewing of children with allegations of having been sexual abused. The first section presents a literature review on the peculiarities of the investigative interviews of pre-school age. Some of the most used investigative interviewing techniques around the globe are presented. Also, some elements that could compromise the child s report during the investigative interview are discussed, such as the use of artifacts (toys and drawings), repetitive interviewing, as well as the type of questions used by the interviewer. In the second section, an empirical study is described focusing on the structure of children s investigative interview, emphasizing the dynamics of questions and answers. The study was based over the document analysis (videos or audio) of a sample 49 real interviews with children aged between six and eleven years old, with allegations of having been sexual abused. The audio-tape or video-tape of the interviews were analyzed and both the questions placed by the interviewer and the answers given by the child were coded. The categories of questions and answers were adapted from pre-existent categories.Only the pre-substantive phase (rapport) and substantive phase (report) of the interviews were considered for the coding of questions and answers, since they are the most relevant phases to the interview. The frequencies of types of questions and types of answers were analyzed, as well as the frequency of each association between type of question and its respective type of answer. The results yielded that the interviewers tended to use few open questions. Most of the interviewers questions were considered appropriate, although more directive (closed question and probing).Therefore children s answers were frequently shorter, which means, with fewer information about what was being investigated. In the concluding section, the results were discussed in terms of the importance of the interviewers training. In addition, results also highlighted the importance of developing need assessment techniques for training investigative interviewers